A Potential Framework For an Impactful Technopreneurship Education - Ratna Mulyany; Syaifullah Muhammad; Teuku Aulia Geumpana; Hendra Halim; Muslim; Miksalmina; Cindy Dwi Pertiwi (Indonesian Journal of Business and Entrepreneurship, 2023)
This study aims to conceptually discuss the potential framework for an impactful technopreneurship education in response to the dynamic business environment. An integrative review based on the selected pertinent literature was utilized to undertake this study. Unlike a systematic review, the integrative review does not aim to cover all articles published on the topic but combines perspectives and insights from different fields or research traditions. Several steps were involved in conducting an integrative review comprising of defining the research questions, conducting a comprehensive search, screening and selecting studies, extracting data and analyzing findings, drawing conclusions and making recommendation. The changes in curriculum and learning processes as well as academic transformation by embedding technological innovation and capacity building are the main priorities in preparing technopreneurs. To prepare reliable technopreneurs, while it is important to focus on technological innovation and capacity building, yet to integrate these two aspects, collaboration is the key word hence the collaboration among universities, the business world, government, media, and the community becomes one of the interesting routes that need to be developed. The pentahelix collaboration plays a major role in the cycle of the technopreneurship from the idea formulation, research, precommercialization, commercialization and embarking the advanced market. Keywords: entrepreneurship, technopreneurship, technological innovation, capacity building, pentahelix collaboration